Control Interno en el Departamento de Crédito-Cobranza de la Cooperativa Innovación Andina Ltda. Provincia de Cotopaxi, Periodo 2012. - Loor Segovia, Jenny Marisol (2014)
This research was conducted in the Savings and Credit Cooperative Innovation Andina Ltda , based in the city of Latacunga, Cotopaxi Province , which had been operating since 2005 , with the aim of contributing to the growth and development partners, particularly those traditionally excluded from the formal banking system marginal rural and urban sectors. The aim of this study is to evaluate the internal control in the Department of Credit & Collection of Cooperative Innovation Cotopaxi Province Andina Ltda , 2012 period , the diagnosis, identify currently allowed , the cooperative has weaknesses in internal control in the Department Credit and Collections , they do not allow you to effectively develop activities because no internal control manual for this area properly applied . Therefore was born the need for an evolution through the system of internal control in order to analyze personnel functions and , the procedures to be followed..….